4t+4=6(12-5t)=

Simple and best practice solution for 4t+4=6(12-5t)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4t+4=6(12-5t)= equation:



4t+4=6(12-5t)=
We move all terms to the left:
4t+4-(6(12-5t))=0
We add all the numbers together, and all the variables
4t-(6(-5t+12))+4=0
We calculate terms in parentheses: -(6(-5t+12)), so:
6(-5t+12)
We multiply parentheses
-30t+72
Back to the equation:
-(-30t+72)
We get rid of parentheses
4t+30t-72+4=0
We add all the numbers together, and all the variables
34t-68=0
We move all terms containing t to the left, all other terms to the right
34t=68
t=68/34
t=2

See similar equations:

| 9(a+4)=194 | | 6/x-5/2x=28 | | 6x-43=5×34 | | 4^6x=16^2x+1 | | 24x=2x+1 | | 40-5x=6.5 | | 5(m+1)=90 | | 3x+-7=5x | | (4/10)+(4/x)=(4/6) | | -12=-11+(n÷-12) | | 2(2x+4)=72 | | 34-4x=3x | | –7f+18=4 | | 2(2x+4)=56 | | -8+2b=20 | | 2x+1(6)=86 | | 2(2x+4)=176 | | 2=(6+k)÷4 | | 2(2x+4)=180 | | (x+5/2)=4.50 | | 11+x=4x-7 | | 6+7x=9+6x | | 8x+6=4x-144 | | 11=-s+15 | | 19.5=(0.5t+14) | | X+105+15+x+x=180 | | 2g+-1=25 | | -18=-5(t+6)–13 | | 4(3x+2)=x+2(x-1) | | 8(z–4)+2=2 | | 5x+4+13+-3x=180 | | 85=x+105 |

Equations solver categories